Genetic variation in Labeo fimbriatus (Cypriniformes: Cyprinidae) populations as revealed by partial cytochrome b sequences of mitochondrial DNA. (3rd May 2016) - Swain, Subrat Kumar; Bej, Dillip; Das, Sofia Priyadarsani; Sahoo, Lakshman; Jayasankar, Pallipuram; Das, Pratap Chandra; Das, Paramananda
Abstract: Labeo fimbriatus, a medium sized carp is assessed as a commercially important aquaculture species in Indian subcontinent. In the present study, the genetic diversity and population structure of four Indian riverine populations of L. fimbriatus have been evaluated using partial cytochrome b sequences of mitochondrial DNA. Sequencing and analysis of this gene from 108 individuals defined 7 distinct haplotypes. Haplotype diversity (Hd) and nucleotide diversity (π) ranged from 0.067 to 0.405 and 0.00023 to 0.03231, respectively. The Mahanadi population had the highest π level. Analysis of molecular variance (AMOVA) indicated that 47.36% of genetic variation contained within population and 53.76% of genetic variation among groups. Pairwise FST analysis indicated that there was little or no genetic differentiation among populations (−0.0018 to 04572) from different geographical regions except Mahanadi population. The Mahanadi population can be considered as a separate stock from rest three riverine populations. Accordingly, the genetic information generated from this study can be implemented while taking decision in formulating base population for the sustainable selective breeding programs of this species.